Orange juice–derived flavanone and phenolic metabolites do not acutely affect cardiovascular risk biomarkers: a randomized, placebo-controlled, crossover trial in men at moderate risk of cardiovascular disease(1)(2)(3)(4)(5) - Schär, Manuel Y (Am J Clin Nutr, 2015)
Background: Epidemiologic data suggest inverse associations between citrus flavanone intake and cardiovascular disease (CVD) risk. However, insufficient randomized controlled trial data limit our understanding of the mechanisms by which flavanones and their metabolites potentially reduce cardiovascular risk factors. Objective: We examined the effects of orange juice or a dose-matched hesperidin supplement on plasma concentrations of established and novel flavanone metabolites and their effects on cardiovascular risk biomarkers in men at moderate CVD risk. Design: In an acute, randomized, placebo-controlled crossover trial, 16 fasted participants (aged 51–69 y) received orange juice or a hesperidin supplement (both providing 320 mg hesperidin) or control (all matched for sugar and vitamin C content). At baseline and 5 h postintake, endothelial function (primary outcome), blood pressure, arterial stiffness, cardiac autonomic function, platelet activation, and NADPH oxidase gene expression and plasma flavanone metabolites were assessed. Before each intervention, a diet low in flavonoids, nitrate/nitrite, alcohol, and caffeine was followed, and a standardized low-flavonoid evening meal was consumed. Results: Orange juice intake significantly elevated mean ± SEM plasma concentrations of 8 flavanone (1.75 ± 0.35 μmol/L, P < 0.0001) and 15 phenolic (13.27 ± 2.22 μmol/L, P < 0.0001) metabolites compared with control at 5 h postconsumption. Despite increased plasma flavanone and phenolic metabolite concentrations, cardiovascular risk biomarkers were unaltered. After hesperidin supplement intake, flavanone metabolites were not different from the control, suggesting altered absorption/metabolism compared with the orange juice matrix. Conclusions: After single-dose flavanone intake within orange juice, circulating flavanone and phenolic metabolites collectively reached a concentration of 15.20 ± 2.15 μmol/L, but no effects were observed on cardiovascular risk biomarkers. Longer-duration randomized controlled trials are required to examine previous associations between higher flavanone intakes and improved cardiovascular health and to ascertain the relative importance of food matrix and flavanone-derived phenolic metabolites. This trial was registered at clinicaltrials.gov as NCT01530893.